Effect of Mesiodistal Angulation of the Maxillary Central Incisors on Esthetic Perception of the Smile in the Frontal View - Alkadhi, Omar Hamad; Alsaif, Reema Abdulaziz; Albukairi, Maha Ali (International Journal of Innovative Research in Medical Science, 2017)
Objective: To evaluate the effect of the mesiodistal angulation of the maxillary central incisors on the esthetic perception of the frontal smile view in young Saudis. Material and Methods: One-hundred and ninety-nine raters evaluated the clinical smiling photographs of one young male and one young female who were chosen according to certain criteria. Frontal smiling photographs of subjects were digitally modified to create 32 photographs of differing mesiodistal angulations of maxillary central incisors. An online survey was formulated, 100 laypeople and 99 dental professionals participated in the rating of photographs using VAS. Statistical analysis was done using independent sample t-test and Dunnet t-test. Results: Statistically significant differences were found between modified incisors angulations scores and the undeviated incisors scores where the undeviated images were more attractive in all photographs for males and females (p<0.05) except for the following angulations: female full face +4°, +8° and -4° and female lower facial third +4° and -4° (p>0.05). Differences between laypeople and dental professionals scores were found in the following angulations: female full face 0° and -8° and female lower facial third 0°, +4° and +8° (p<0.05). Full face images scores and lower facial third images scores were different in the following angulations: male -8°, +8° and +16° and female 0° (p<0.05).